Asymmetric Synthesis of 2,3,6-Trisubstituted Piperidines via Baylis–Hillman Adducts and Lithium Amide through Domino Reaction - Salgado, Mateo M.; Manchado, Alejandro; Nieto, Carlos T.; Díez, David; Garrido, Narciso M. (Synlett, 2020)
A convenient asymmetric synthesis of methyl (2S,3S,6R)-6-(4-fluorophenyl)-2-(4-hydroxyphenyl)-piperidine-3-carboxylate is described, starting from Baylis–Hillman adducts. The route involves a domino process: allylic acetate rearrangement, stereoselective Ireland–Claisen rearrangement and asymmetric Michael addition, which provides a δ-amino acid derivative with full stereochemical control. A subsequent chemoselective transformation of one of the side-chain groups allows an effective cyclization leading to biologically interesting polysubstituted piperidines in which the 2,6-aryl groups could be attached sequentially.
Keywords: δ-amino acids; asymmetric synthesis; Michael addition; domino reaction; Ireland–Claissen rearrangement; Baylis–Hillman adducts; piperidines; Weinreb amide